Low level myocardial parvovirus B19 persistence is a frequent finding in patients with heart disease but unrelated to ongoing myocardial injury - Lotze, Ulrich; Egerer, Renate; Glück, Brigitte; Zell, Roland; Sigusch, Holger; Erhardt, Christian; Heim, Albert; Kandolf, Reinhard; Bock, Thomas; Wutzler, Peter; Figulla, Hans-R (Journal of medical virology, 2010)
While myocardial parvovirus B19 (B19V), aside from enteroviruses (EV) and adenoviruses (ADV), has recently been found often in patients with myocarditis and idiopathic dilated cardiomyopathy (IDC), the pathogenetic significance of B19V genomes in those patients has not yet been sufficiently elucidated. In the present study, left ventricular endomyocardial biopsies from 24 patients with left ventricular ejection fraction (LVEF) below 55% due to IDC, and tissue from the right atrial appendage of 10 control patients undergoing bypass surgery with normal LVEF (>55%) were investigated for B19V, ADV, and EV genomes by specific nested polymerase chain reaction (PCR), by real time PCR or by reverse-transcription PCR, respectively. The myocardial tissue samples from the 10 controls were analyzed each in three different virological laboratories for B19V. In the IDC group, the frequency of the myocardial virus genomes found in 54% (13/24) of the patients was as follows: B19V: 50% (12/24), EV: 8% (2/24), including one patient with B19V and EV, and ADV: 0% (0/24). For comparison, the prevalence of B19V genomes was between 30% and 60% in the control group as detected in three different laboratories, but all these control subjects were EV- and ADV-negative. The number of B19V gene copies, however, was very low and similar both in the IDC and control group. In the majority of patients myocardial B19V persistence was associated with a low virus load irrespective of the underlying heart disease so that it may be of no importance in the pathogenesis of IDC. J. Med. Virol. 82:1449-1457, 2010.